Performance Assessment of Extension Workers and Allowances in the Perspective of Ijārah ‘Ala Al-‘Amal - Maulidia, Reihan Putri; Bakar, Ali Abu; Reza, T. Surya (IAIN Manado, 2025)
This study aims to analyse the performance appraisal system of religious instructors at the Ministry of Religious Affairs, Bener Meriah Regency, in relation to the realisation of performance allowances (tukin), viewed from the perspective of the ijārah ‘ala al-‘amal contract. The study was motivated by a tendency in performance assessment that previously emphasised administrative aspects, such as report completeness and attendance, rather than the effectiveness of guidance and the tangible impact of religious counselling in the community. This research employs a qualitative approach with a descriptive analytical method and an empirical juridical type of study. Primary data were obtained through interviews, while secondary data were derived from regulations, positive legal literature, and both classical and contemporary fiqh al-mu‘āmalah sources. The findings indicate that after the enactment of the Director General of Islamic Community Guidance Decree No. 794 of 2025, the performance assessment system shifted from an administrative orientation to a results-based model through the e-Kinerja. This shift encourages a more proportional evaluation that reflects actual work outcomes. Nevertheless, differences in assessment instruments among instructors persist due to social and geographical factors. Overall, the new system is more aligned with the principle of justice in the ijārah ‘ala al-‘amal contract, although further refinement is required to ensure that work benefits are measured fairly and contextually.